Harmony in transition: Navigating academic, well-being, and sociocultural landscapes in the United Kingdom - Christidis, Angela (Journal of International Students, 2026)
This mixed-methods study explores the academic, sociocultural, and well-being experiences of Chinese international students in UK higher education. Drawing on questionnaires, interviews, and focus groups, the research identifies a phased adjustment process: initial navigation of academic expectations, followed by relational consolidation through peer networks and subsequent expansion into sociocultural engagement and academic agency. These interconnected domains are associated with reported personal and professional development. Participation in sociocultural initiatives at different stages was associated with varied experiences, depending on students’ developmental readiness. Students entering via pre-sessional English programs reported uneven preparedness, indicating the importance of sustained academic mentoring. Accounts of mental health challenges point to the relevance of culturally responsive, community-based support alongside traditional counseling services. The results position informal institutional spaces as developmental mechanisms rather than supplementary supports. The study offers evidence-based recommendations for phased support strategies and inclusive pedagogy to enhance long-term academic integration, sociocultural engagement, and well-being.